2006
DOI: 10.1002/ajhb.20499
|View full text |Cite
|
Sign up to set email alerts
|

Preference for sons and sex ratio in two non‐western societies

Abstract: Moroccan Berbers and the Bolivian Aymara are two unrelated peasant groups living in adverse environments with a still rather traditional agriculture. Precarious life conditions may be responsible for the importance given to male labor and hence for the cultural preference conferred on male descent. This preference, expressed in the social valorization of sons to the detriment of daughters, is more emphasized if the socioeconomic status of the family is lower. Interpreted according to the cost/benefit approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
(27 reference statements)
0
14
0
Order By: Relevance
“…On the basis of a study of gender biases among the Mukogodo of Kenya, Cronk [20] suggested that favouritism towards daughters occurred as a result of lowered socio-economic status. However, there are also studies that report greater social valorisation of sons at the detriment of daughters [21], including dietary discrimination [22], thereby dispelling conclusions of a nutritionally advantaged position of female over male children.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of a study of gender biases among the Mukogodo of Kenya, Cronk [20] suggested that favouritism towards daughters occurred as a result of lowered socio-economic status. However, there are also studies that report greater social valorisation of sons at the detriment of daughters [21], including dietary discrimination [22], thereby dispelling conclusions of a nutritionally advantaged position of female over male children.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence in stunting among boys as compared to girls is in agreement with the literature on stunting in sub-Saharan Africa [11], but the improvement over time in boys, more so than in girls, is difficult to explain. Looking to family dynamics, the literature on parental sex bias in relation to child care and feeding practices is contradictory and the evidence for bias is scarce [12,13,35]. DHS data have been brought to bear on this subject, but only via indirect inferences based on parental education differences [35].…”
Section: Discussionmentioning
confidence: 99%
“…In sub-Saharan Africa, boys have consistently posted higher rates of stunting compared to girls [11]. Many (sometimes contradicting) reasons have been hypothesized to explain the sex difference, such as gender-differentiated feeding practices [12,13]. It is also postulated that girls are physically less active and therefore spend less energy compared to boys, and that boys are more vulnerable to acute respiratory infection and diarrhoea [14].…”
Section: Introductionmentioning
confidence: 99%
“…For humans, differences in reproductive investment may take the form of neglect of offspring of one sex (usually females), including infanticide and sex-specific abortions (Wilcox and Baird, 2011), differential nursing frequency by offspring sex, or longer overall breastfeeding durations prior to weaning, as well as increased volume transfer of milk, all largely behavioral differences in offspring rearing. While these behavioral differences vary within and between populations, the overall impact in some populations (excluding outright neglect) may be marginal (Crognier, 2006). Humans do, however, reflect an unusual application of sex-based differences in offspring investment, as reproductive investment by offspring sex may be highly variable independent of maternal condition or resources and likely reflect variable social beliefs and practices rather than biological differences.…”
Section: Introductionmentioning
confidence: 91%